Influence of dietary supplementation with new Lactobacillus strains on hematology, serum biochemistry, nutritional status, digestibility, enzyme activities, and immunity in dogs - Sathita Areerat; Pipatpong Chundang; Pornsucha Palaseweenun; Nattaphong Akrimajirachoote; Jaruwan Sitdhipo; Punnathorn Thaveethaptaikul; Pennapa Chonpathompikunlert; Kanidta Niwasabutra; Pongsathon Phapugrangkul; Attawit Kovitvadhi (Veterinary World, 2023)
Background and Aim: The use of antibiotics is associated with many side effects, with the development of bacterial resistance being particularly important. It has been found that dogs and their owners host similar resistant bacteria. This contributes to increased concurrent bacterial resistance and a possible trend of increased bacterial resistance in humans. Thus, using probiotics in dogs is an alternative option for preventing and reducing the transmission of bacterial resistance from dogs to humans. Probiotics are characterized by their potential to endure low pH levels and high concentrations of bile acids in the gastrointestinal tract. Lactobacilli are more acid-tolerant and resistant to bile acid, so they are ideal probiotics to be added to the canine diet. According to the previous studies, the benefits of Lactobacillus are a stable nutritional status and greater digestibility, along with improved fecal scores and reduced ammonia in dogs. However, no studies have been conducted with Lactobacillus plantarum CM20-8 (TISTR 2676), Lactobacillus acidophilus Im10 (TISTR 2734), Lactobacillus rhamnosus L12-2 (TISTR 2716), Lactobacillus paracasei KT-5 (TISTR 2688), and Lactobacillus fermentum CM14-8 (TISTR 2720), or their use in combination. Hence, the aim of this study was to examine the possible effects of the aforementioned Lactobacillus on hematological indices, nutritional status, digestibility, enzyme activities, and immunity in dogs. From the results, a new and safe strain of Lactobacillus may emerge for use as a probiotic in the future.